A smart, multi-configuration, and low-cost system for water turbidity monitoring - Alessio Vecchio; Monica Bini; Marco Lazzarotti; Marco Luppichini; Maurizio Palmieri (Results in Engineering)
Measuring the amount of suspended sediment in rivers is important for a better understanding of phenomena like soil erosion or floods. Since such phenomena are not spatially homogeneous, a distributed measurement approach is required to obtain fine-grained and realistic models. We designed and implemented a low-cost, flexible, and smart suspended sediment concentration monitor. The system only uses components that are easy to find and assemble. This, together with the reduced costs, enables the use of multiple instances for distributed monitoring. The system can operate according to different configurations, fixed or mobile, and using a variety of connection technologies, to possibly cover the various necessities that arise from the diverse installation sites. Each measuring unit automatically retrieves its operational parameters, easing the configuration of a possibly large distributed measurement system.